Political and Cultural Background of Kerala Temples: Exploring the Evolution of Kerala Temples and their Socio-Economic Impact (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Kerala, however framed a piece of Tamil full scale district, has a great deal of biological distinction from it in the agro-climatic zone as far as seasons, precipitation, scene, soil structure, penetrability, maintenance, versatility et cetera. The wet rice scene eco framework has abundance of water as opposed to advance Tamilakam. Henceforth, the innovation and work process fluctuated in like manner. The presence of created innovation of water administration, information of season and routine with regards to paddy agribusiness and an initiative with coercive social control and suitable institutional ideological methods for vast activation, division and acknowledgment of work was need of the local biological system to wind up a feasible beneficial land. The change of individual Brahmana family unit into organization was the consequence of these requirements. In this unique circumstance, excite in Kerala new arrangements of land holding and landless which in the long run got intervened by mediators to frame complex structure, portrayed by specific division of work transforming into genetic occupations and non-financial coercive modes of social acknowledgment.